D'un atelier de moulage à un autre: les migrations des mouleurs originaires des Forges du Saint-Maurice et la segmentation du marché du travail nord-américain, 1851-1884 - Bischoff, Peter (Labour / Le travail, 1997)
issued: 1997-23-00
Keywords: Fer et acier; Mouleurs

Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 1996)
Keywords: Travail

Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2002)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2007)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2014)
Keywords: Travail

Le travail et la classe ouvrière montréalaise au XIXe siècle - Petitclerc, Martin (Histoire de Montréal et de sa région, 2012)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

Ethnic Partition of the Work Force in 1840s Montréal - Olson, Sherry (Labour / Le travail, 2004)
Keywords: Anglophones; Britanniques; Français; Irlandais; Protestants; Travail

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

La nature des procès de travail à Montréal entre 1790 et 1830 - Tremblay, Robert (Université de Montréal, 1979)
Keywords: Artisans

Unfair Masters and Rascally Servants? Labour Relations among Bourgeois, Clerks and Voyageurs in the Montréal Fur Trade, 1780-1821 - Podruchny, Carolyn (Labour / Le travail, 1999)
Keywords: Bourgeoisie; Engagés; Fourrure

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

Working-Class Experience: Rethinking the History of Canadian Labour, 1800-1991 - Palmer, Bryan D. (McClelland & Stewart, 1992)
Keywords: Travail

L'histoire des cols bleus regroupés de Montréal. Tome 1: De ses origines à 1963 - Lapierre, Jean (2008)
Keywords: Travail

Enforcement in Apprenticeship Contracts: Were Runaways a Serious Problem? Evidence from Montreal - Hamilton, Gillian (Journal of Economic History, 1995)
Number: 3
Keywords: Apprentissage; Travail

Apprenticeship in Early Nineteenth Century Montreal, 1790-1812 - Audet, Pierre-H. (Université Concordia, 1975)
Keywords: Apprentissage; Travail

Compassion, association, utopie. La mutualité ouvrière à Montréal au milieu du XIXe siècle - Petitclerc, Martin (Revue du MAUSS, 2008)
Number: 32
Keywords: Assurance; Travail

The Law of Servants and the Servants of the Law: Judicial Regulation of Labour Relations in Montreal, 1830-1845 - Pilarczyk, Ian C. (Université McGill, 1997)
Keywords: Droit; Travail

Wage Disputes and the Courts in Montreal, 1816-1835 - Laing Hogg, Grace; Shulman, Gwen (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Travail; Tribunaux

The Decline of Apprenticeship in North America: Evidence from Montreal - Hamilton, Gillian (Journal of Economic History, 2000)
Number: 3
Keywords: Apprentissage; Travail

Les jardiniers professionnels de Montréal au XVIIIe siècle - Fortin, Guillaume (Université du Québec à Montréal, 2019)
Keywords: Jardins; Travail

Par monts et par vaux. Migrants canadiens-français et italiens dans l’économie nord-atlantique, 1860-1914 - Ramirez, Bruno (Boréal, 1991)
Keywords: Italiens; Travail

On the Move: French-Canadian and Italian Migrants in the North Atlantic Economy, 1860-1914 - Ramirez, Bruno (McClelland and Stewart, 1991)
Keywords: Italiens; Travail

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-24-00
Keywords: Famille; Recensements; Travail

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; Parcs; Travail

L’émergence d’un mouvement. Les premières sociétés de secours mutuels canadienne-française à Montréal, (1851-1867) - Bischoff, Peter C. (Cap-aux-Diamants, 2018)
issued: 2018-23-00
Keywords: Assurance; Travail; Union Saint-Joseph

Parent, Lanctôt et Helbronner. Trois figures de l’économie sociale au XIXe siècle - Petitclerc, Martin (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Helbronner; Jules; Lanctôt; Médéric; Travail

Working-Class Experience: the Rise and Reconstitution of Canadian Labour, 1800-1980 - Palmer, Bryan D. (Butterworth, 1983)
Keywords: Chevaliers du Travail; Grèves; Syndicats internationaux

Labour and the Montreal Working Class in the Nineteenth Century - Petitclerc, Martin (Montreal: The History of A North American City, 2018)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Leméac, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives - Fyson, Donald; M. Coates, Colin; Harvey, Kathryn (Groupe d'histoire de Montréal, 1993)
Keywords: Criminalité; Mariage; Police; Prostitution; Travail; Tribunaux

Chronique de l'industrie de la chaussure dans Hochelaga-Maisonneuve - Carrera, Jose David (D'une trac à l'autre, 1990)
Number: 1
Keywords: Artisans; Chaussure; Hochelaga (quartier); Maisonneuve; Quartiers; Travail

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Le syndicalisme québécois: deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Fédération des travailleurs et travailleuses du Québec (FTQ); Grèves; Travail

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

"Ils ne sont plus le peuple qu’ils étaient hier": la culture ouvrière à Montréal-Est au moment de la Confédération - Petitclerc, Martin; Bellavance, Claude; St-Hilaire, Marc (Le fait urbain, 2020)
Keywords: Cartier; Georges-Étienne; Lanctôt; Médéric; Montréal-Est; Partis politiques; Quartiers; Rouges; Saint-Jacques; Saint-Louis; Sainte-Marie; Travail; Élections

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
issued: 2008-23-00
Keywords: Lachine; Émeutes

The Growth of a Craft Labour Force: Montreal Leather Artisans, 1815-1831 - Burgess, Joanne (Canadian Working Class History: Selected Readings, 1992)
Keywords: Artisans; Tannerie

Souvenirs sur les commencements de l'Union St-Joseph de Montréal - Plinguet, J. A. (Plinguet et Laplante, 1866)
Keywords: Assurance; Union Saint-Joseph

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

La grève des charretiers à Montréal, 1864 - Heap, Margaret (Revue d'histoire de l'Amérique française, 1977)
Number: 3
Keywords: Charretiers; Grèves

Les domestiques en milieu urbain au début du XIXe siècle - Lacelle, Claudette (Parcs Canada, 1980)
Keywords: Domestiques; Femmes

La grève des charretiers à Montréal, 1864 - Heap, Margaret (Le mouvement ouvrier au Québec, 1980)
Keywords: Charretiers; Grèves

The Growth of a Craft Labour Force: Montréal Leather Artisans, 1815-1831 - Burgess, Joanne (CHA / SHC, Historical Papers / Communications historiques, 1988)
Keywords: Artisans; Chaussure; Sellerie; Tannerie

Dimensions of Paternalism: Discipline and Culture in Canadian Railway Operations in the 1850s - Craven, Paul; Traves, Tom (On the Job: Confronting the Labour Process in Canada, 1986)
Keywords: Chemins de fer; Grand Tronc

La formation matérielle de la classe ouvrière à Montréal entre 1790 et 1830 - Tremblay, Robert (Revue d'histoire de l'Amérique française, 1979)
Number: 1
Keywords: Artisans

The Lachine Strike of 1843 - Pentland, H. C. (Canadian Historical Review, 1948)
Number: 3
Keywords: Grèves; Irlandais; Lachine (canal)

Early Trade Unionism in Quebec - 1833-1834: the Carpenters' and Joiners' General Strike in Montreal - Vance, C. (The Marxist Quarterly, 1962)
issued: 1962-23-00
Keywords: Charpentiers; Grèves; Menuisiers

Les pionniers du mouvement ouvrier au Québec: quelques pistes de réflexion sur la première génération de militants des années 1830 - Tremblay, Robert (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
issued: 2012-21-00
Keywords: Charpentiers; Chaussure; Confection; Imprimerie; Menuisiers

Baptizing Novices: Ritual Moments among French Canadian Voyageurs in the Montreal Fur Trade, 1780-1821 - Podruchny, Carolyn (Canadian Historical Review, 2002)
Number: 2
Keywords: Fourrure

Des emplois pour une élite cultivée: travailler pour l’Assemblée législative de la province du Canada, 1840-1850 - Roy, Alain (Bulletin d'histoire politique, 2017)
Number: 3
Keywords: Fonctionnaires; Parlement

Du forgeron au machiniste: l'impact social de la mécanisation des opérations d'usinage dans l'industrie de la métallurgie à Montréal de 1815 à 1860 - Tremblay, Robert (Université du Québec à Montréal, 1992)

SHEARER, JAMES - McNally, Larry S. (Dictionnaire biographique du Canada, 1994)

DARLINGTON, WILLIAM - Rouillard, Jacques (Dictionnaire biographique du Canada, 1998)

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Number: 2
Keywords: Grèves; Irlandais; Lachine (canal)

MONTFERRAND, dit Favre, JOSEPH - Goyer, Gérard; Hamelin, Jean (Dictionnaire biographique du Canada, 1977)

Les ouvriers mouleurs à Montréal, 1859-1881 - Bischoff, Peter (Université du Québec à Montréal, 1986)
Keywords: Fer et acier; Mouleurs

La formation des traditions de solidarité ouvrière chez les mouleurs montréalais: la longue marche vers le syndicalisme (1859-1881) - Bischoff, Peter (Labour / Le travailleur, 1988)
issued: 1988-21-00
Keywords: Fer et acier; Mouleurs

Tensions et solidarité: la formation des traditions syndicales chez les mouleurs de Montréal, Hamilton et Toronto, 1851 à 1893 - Bischoff, Peter (Université de Montréal, 1992)
Keywords: Fer et acier; Mouleurs

PAQUETTE, WILFRID (Dictionnaire biographique du Canada, 1998)

BENOÎT, OLIVIER-DAVID - Rouillard, Jacques (Dictionnaire biographique du Canada, 1990)

WARREN, GEORGE STEPHENS - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

GUIBORD, JOSEPH - Rioux, Jean-Roch (Dictionnaire biographique du Canada, 1977)

The Segregated City: Class and Occupation in Montreal 1861-1901/La ville différenciée: professions et classes sociales à Montréal, 1861-1901 - Lewis, Robert D. (Université McGill, Département de géographie, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Segregated City: Residential Differentiation, Rent and Income in Montreal, 1861-1901 - Lewis, Robert D. (Université McGill, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

Some Early Teachers' Associations in Quebec - Cooper, John Irwin (Educational Record of the Province of Quebec, 1964)
Keywords: Enseignants; Hicks; William Henry; Lower Canada Teachers' Association

The Size of the Labour Force in the Montreal Fur Trade, 1675-1790: A Critical Evaluation - Murphy, Brian D. (Université d'Ottawa, 1986)
Keywords: Engagés; Fourrure

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

Artisans et ouvriers à l’époque des revendications démocratiques et nationalitaires du Parti patriote dans le Bas-Canada, 1832-1838: un rendez-vous manqué avec l’histoire ? - Tremblay, Robert (Bulletin d'histoire politique, 2017)
Number: 2
Keywords: Partis politiques; Tracey; Daniel; Élections

RODIER, JOSEPH-ALPHONSE - Rouillard, Jacques (Dictionnaire biographique du Canada, 1994)

ARCHAMBAULT, LOUIS - Comeau, Robert (Dictionnaire biographique du Canada, 1994)

Des Forges du Saint-Maurice aux fonderies de Montréal: mobilité géographique, solidarité communautaire et action syndicale des mouleurs, 1829-1881 - Bischoff, Peter (Revue d'histoire de l'Amérique française, 1989)
issued: 1989-22-00
Keywords: Artisans; Famille; Fer et acier; Mouleurs

Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Number: 68
Keywords: Britanniques

"Traveling the Country 'round": migrations et syndicalisme chez les mouleurs de l'Ontario et du Québec membres de l'Iron Molders Union of North America, 1860 à 1892 - Bischoff, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
Number: 1
Keywords: Fer et acier; Iron Molders Union of North America; Mouleurs

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

L'industrie de la chaussure à Montréal 1840-1870: de l'artisanat à la fabrique - Burgess, Joanne (Université du Québec à Montréal, 1977)
Keywords: Artisans; Chaussure

Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Les métiers du cuir, 1981)
Keywords: Artisans; Chaussure

Tensions et solidarité: la formation des traditions syndicales chez les mouleurs de Montréal, Hamilton et Toronto, 1851 à 1893 - Bischoff, Peter (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
issued: 1992-24-00
Keywords: Fer et acier; Mouleurs

Saving the Union's Jack: The Montreal Sailor's Institute and the Homeless Sailor, 1862-98 - Ingram, Darcy (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)

L'industrie de la chaussure à Montréal: 1840-1870 - Le passage de l'artisanat à la fabrique - Burgess, Joanne (Revue d'histoire de l'Amérique française, 1977)
Number: 2
Keywords: Artisans; Chaussure

À chacune son rang. Les ''filles données'' des Soeurs Grises 1855-1905 - Gervais, Diane (Revue d'histoire de l'Amérique française, 2014)
issued: 2014-22-00/2014-23-00
Keywords: Communautés religieuses; Domestiques; Femmes; Soeurs Grises

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (McGill-Queen's University Press, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

VERVILLE, ALPHONSE - Leroux, Éric (Dictionnaire biographique du Canada, 2005)

DUBREUIL, VICTOR - Rouillard, Jacques (Dictionnaire biographique du Canada, 1998)

JULIEN, HENRI - Guilbault, Nicole (Dictionnaire biographique du Canada, 1994)

LESPÉRANCE, ZOTIQUE - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Butcher, Baker, Cabinetmaker? A View of Montreal's Scottish Immigrant Community from 1835 to 1865 - McNabb, Heather (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Écossais

FILIATREAULT, ARISTIDE - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1998)

HÉBERT, LOUIS-PHILIPPE - Lacasse, Yves (Dictionnaire biographique du Canada, 1998)

DRUMMOND, GEORGE EDWARD - Tremblay, Robert (Dictionnaire biographique du Canada, 1998)

HELBRONNER, JULES - de Bonville, Jean (Dictionnaire biographique du Canada, 2005)

LAFONTAINE, URBAIN - Rouillard, Jacques (Dictionnaire biographique du Canada, 1998)

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Le Montréal religieux - Chaussé, Gilles (Montréal, 1642-1992, 1992)

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
issued: 2010-24-00
Keywords: Confection; Femmes

Le règne de la scientificité: histoire de l'étiologie des maladies infectieuses dans la presse médicale du Québec, 1840-1880 - Beaudry, Louka (Université de Montréal, 2013)
Keywords: Médecine

McKERGOW, JOHN - Otis, Yves (Dictionnaire biographique du Canada, 1998)

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

GUYON, LOUIS - Dionne, Jean-Claude (Dictionnaire biographique du Canada, 2020)

CYR, LOUIS - Ohl, Paul (Dictionnaire biographique du Canada, 1998)

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

LAPORTE, sir HORMISDAS - Poitras, Claire (Dictionnaire biographique du Canada, 2018)

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)